Social Challenges of Technological Singularity. The Complexification of the Humano-Virtual Reality - Klauza, Karol; Gruchoła, Małgorzata (Roczniki Kulturoznawcze, 2025)
Modern technologies develop primarily under the influence of cognitive, economic, and cultural motivations. A key social challenge is balancing the benefits and potential threats to humanity. Therefore, the ethical criterion must be considered in the process of discovering and utilizing these technologies. This primarily concerns sustainable development while maintaining the axiological paradigms of civilization, shaped within the Greco-Roman tradition. This implies a positive attitude towards technological progress in the name of preserving the anthropological primacy. One of the philosophical contexts relevant to this approach may be 20th-century Teilhardism.